TANGGUNG JAWAB PT GOJEK INDONESIA DALAM PENGIRIMAN BARANG KONSUMEN DARI SEGI UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI KASUS KURIR GOJEK MEMBAWA LARI SMARTPHONE TAHUN 2017). - Lidya Fazriani; Jeane Neltje Saly (Jurnal Hukum Adigama, 2019)
Shipping goods using postal expedition services is a conventional thing in the modern era. Short-distance shipping is currently being replaced more by online shipping services, such as Gojek. Gojek Indonesia offers Go-send items for people who want to send. But in line with that, the weakness of law and material in the regulation of Gojek policy resulted in the lack of implementation of legal certainty. This paper was prepared to be able to answer how accountability is given to users of Gojek Services in Indonesia and what forms of compensation provided by Gojek for claim of loss of goods that occur in Go-send services fered. This paper aims to provide a description of the right of users and the obligation that must be fulfilled by Gojek itself and explain the forms of compensation made by the gojek as a form of accountability for complaints of the use of Go-Send services. The method used is a normative legal research method that is supported by a legal approach, an analytical and conceptual approach, and a case approach. The final result of the preparation of this jurnal is the responsibility given to consumers for the loss of goods in the services offered by providing compensation and forms of compensation that are judicially determined as competation in the form of money as a form of nominal liability and compensation through shares or similar items.